FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENCEGAHAN ANEMIA PADA IBU HAMILDI PUSKESMAS LHOKSUKON KABUPATEN ACEH UTARA - Yunita, Mawarni; Suryantara, Bima; Subaris Kasjono, Heru (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2026)
The prevalence of anemia at <8 weeks gestation was 40%, 9-12 weeks gestation was 46.9%, 13-16 weeks gestation was 50%, 17-20 weeks gestation was 52.9%, 21-24 weeks gestation was 68.3% and >25 weeks gestation was 64.6%. According to WHO in 2020, the prevalence of pregnant women who experience Fe deficiency anemia is around 35-75% which increases with increasing gestational age. The research design used was an analytic survey with a cross-sectional approach. The population and sample in this study amounted to 54 people. Total sampling technique. Univariate and bivariate data analysis with frequency distribution tables.Between education and anemia prevention behavior, the p value (sig) =0.621> 0.05 means that there is no relationship between education and anemia prevention behavior. Statistical test results obtained p (sig) =0.851> 0.05 which means there is no relationship between work and anemia prevention behavior. Statistical test results obtained p (sig) =0.000> 0.05 which means there is a relationship between knowledge and anemia prevention behavior. The statistical test results obtained p (sig) =0.005 <0.05 which means there is a relationship between attitude and anemia prevention behavior. The statistical test results obtained p value (sig) =0.192 <0.05 which means there is a relationship of trust with anemia prevention behavior. The statistical test results obtained p (sig) =0.000 <0.05, which means that there is a relationship between husband/family support and anemia prevention behavior. The results of the statistical test obtained a p value (sig) = 0.232 < 0.05, which means that there is no relationship between support from health workers and anemia prevention behavior. of the 3 variables tested by multiple logistic regression in the first stage, two variables have a p-value <0.05 and the largest is the knowledge variable (p=0.000). This means that the most dominant variable associated with anemia prevention behavior is knowledge. The most dominant variable associated with anemia prevention behavior is knowledge.